Artificial Intelligence-Based Interactive Learning Media for Improving Reading Comprehension in Elementary Education - Nining Widyah Kusnanik; Lalu Ibrohim Burhan (PT. LIB Research Cendekia, 2026)
This study investigates the effectiveness of Artificial Intelligence (AI)-based interactive learning media in improving elementary school students' reading comprehension within a technology-enhanced learning environment. The increasing integration of AI in education has created opportunities to develop adaptive, data-driven, and interactive instructional systems that support personalized learning. However, empirical studies examining the impact of AI on elementary-level reading comprehension remain limited. This study employed a quasi-experimental design with a pretest–posttest control group approach involving 60 fourth-grade students from a public elementary school in East Lombok Regency, Indonesia. Participants were divided into an experimental group that received AI-supported reading instruction and a control group that received conventional reading instruction. Data were collected using a reading comprehension test consisting of 30 items, student response questionnaires, and classroom observations. Quantitative data were analyzed using descriptive statistics, paired-sample and independent-sample t-tests, normalized gain (N-gain) analysis, and effect size calculations. In contrast, qualitative data were examined through thematic analysis. The results indicate that students exposed to AI-based interactive learning media demonstrated significantly greater improvements in reading comprehension than those receiving traditional instruction. The greatest learning gains were observed in higher-order comprehension skills, particularly inferential reasoning and summarizing ability. Additionally, students reported positive perceptions of the AI-supported learning environment, highlighting the role of adaptive feedback and interactive tasks in fostering comprehension. These findings suggest that AI-based interactive learning media can effectively enhance elementary students' reading comprehension and offer a promising approach to strengthening literacy instruction in technology-enhanced learning environments.